ILLOCUTIONARY ACTS ON ALADDIN MOVIE 2019 - Wulan Angelia Sembiring; Ambalegin Ambalegin (Universitas Putera Batam, 2019)
Illocutionary act is a part of pragmatics studies. Illocutionary acts are acts performed by speakers in saying something (with an appropriate intention and in an appropriate context), The aim of this research were to find out the types of illocutionary act in the Aladdin movie and also to find context underlying illocutionary act in the movie .This method was descriptive qualitative because the data were the utterances of the characters in the Aladdin movie. The research colleting the data with non-participatory methods .There were some steps in collecting the data: downloading the movie script, watching the movie several times, reading and observing the dialogue in the movie .The result of the research there are 30 utterances of directives illocutionary acts . Each of the utterances divided into a part of directive illocutionary act . The data were classified into five namely are , directives (10), assertives (5) declaratives (2), commissives (4), expressives (9).